Effectiveness Combination of Zumba and HIIT through Peer Group Online Class on Physical Fitness and Waist Circumference of Youth - Purwaningtyas, Desiani Rizki; Fitriani, Anna; Birwin, Alib (Lembaga Penerbitan Unversitas Esa Unggul, 2024)
Peer support is an effective mediator for promoting physical activity and reducing sedentary behavior in adolescent. Zumba is one of popular exercise but light effect on some physical fitness indicator. HIIT had great effect in improving physical fitness. The purpose of this study was to compare physical fitness and waist circumference effect of peer group online zumba dance, with or without HIIT of youth. There were three group: 1) control, 2) zumba, and 3) zumba and HIIT. Each group consists of 30 subjects who are members of peer group. Intervention exercise training was doing for seven weeks with three sessions exercise every week. Duration for zumba dance and HIIT were 30 and seven minutes per session. The control group didn’t get any physical exercise treatment. All of group also received online class about fitness nutrition education. Cardiorespiratory fitness, muscular endurance, and muscular strength were physical fitness component which had been assessed. Significant improvement between baseline and endline on all of variables were observed in intervention groups both zumba group and zumba + HIIT group. There were significant differences on cardiorespiratory endurance and muscular endurance in both of intervention groups compare to control group at endline. Significant difference on waist circumference just between zumba + HIIT and control group at endline. Both exercise intervention significantly changed cardiorespiratory and muscular endurance. Combination of zumba + HIIT is effective to improve muscular strength and waist circumference compared to zumba without HIIT.Keywords: Zumba, HIIT, VO2max, muscular fitness